L’évaluation certificative en éducation physique et à la santé : pratiques et défis déclarés des enseignants - Bezeau, David; Savard, Maïa; Lemieux, William (Canadian Journal of Education/Revue canadienne de l'éducation, 2025)
Summative assessment in physical education is an important issue. This study attempts to better understand the summative assessment process in physical and health education (PHE) and to identify its main challenges. Data to meet these objectives were collected from PE teachers through individual interviews (n = 11) and look-alike interviews (n = 10). The description of the participants’ assessment process highlights a diversity of practices, strategies and tools mobilized in the planning, information gathering, interpretation and grading phases, but also several important challenges experienced by PHE teachers.